Ketahanan Pangan Masyarakat Berpendapatan Rendah di Jawa Tengah dan Nusa Tenggara Barat - Handewi P.S. Rachman; Sri Hastuti Suhartini (Jurnal Agro Ekonomi, 1996)
The prime objective of the study is to investigate food security at micro level (household). Data were derived from National Socio Economic Survey (SUSENAS) 1987 and 1990 and also primary data from agricultural household surveys in rural Central Java and West Nusa Tenggara (NTB). Analysis result showed that there were some food shortage at household level although at national and regional levels the food security was quite established. By categorizing household with food expenditure share of 80 percent to total expenditure as low food security by household, SUSENAS data revealed that between 1987 and 1990 the household with low food security category in Central Java and NTB decreased from 10 to 8 percent and from 27 to 18 percent of the total households. Households with low food security category were characterized by low education attainment of household head and his spouse (less than 3 years) with average household expenditure in 1990 of Rp 15.000,-/capita/month in Central Java and Rp 18.000,-/capita/month in NTB. Case studies in Sragen and Cilacap Districts (Central Java) and Central Lombok in NTB showed that food shortage at sample's household level had varied between once to four times a year. Influencing factors of household food security were among others: income level (purchasing power) and food prices. Government's and/or private body's subsidies were required besides efforts done by the households themselves concerning the existing reality in overcoming food shortage at household level. The subsidies were badly needed reminding that generally households with low food security category facing food shortage owned very much limited resources holding.